Sinergitas Perbankan dan Financial Technology: Ikhtiar Menuju Inklusivitas Keuangan Masyarakat Unbankable - Abdul Aziz; Dini Maulana Lestari; Reni Furwanti (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Financial technology era is forced such financial institutions become digitalize in today’s world regarding to increasing financial inclusion and empowering unbanked societies. Nevertheless, this phenomenon is not override the function of bank which is the earlier financial institution that is splashing around in the term of financial inclusion. Actually, those two financial institutions have such strengthen and weakness in order to operate their primary activities in the term of funding and financing, thus, if banking and financial institutions are collaborating it could be fulfilled their main function each other regarding to rising up such financial inclusion of unbanked society. This research discusses the cooperation between banking and financial technology institutions in order to increase financial inclusion of unbanked society. Also, this is kind of qualitative descriptive research through the philosophy of positivism approach. As the result, this research delineates if bank and financial technology institutions are collaborating it could increase the rate of financial inclusion of unbanked citizens effectively and efficiently, not only that, but it would worth for those two institutions in the term of operational.